Cross-Device Interaction via Micro-mobility and F-formations - Marquardt, Nicolai; Hinckley, Ken; Greenberg, Saul (UIST '12 Proceedings of the 25th annual ACM symposium on User interface software and technology, 2012)
GroupTogether is a system that explores cross-device interaction using two sociological constructs. First, F-formations concern the distance and relative body orientation among multiple users, which indicate when and how people position themselves as a group. Second, micro-mobility describes how people orient and tilt devices towards one another to promote fine-grained sharing during co-present collaboration. We sense these constructs using: (a) a pair of overhead Kinect depth cameras to sense small groups of people, (b) low-power 8GHz band radio modules to establish the identity, presence, and coarse-grained relative locations of devices, and (c) accelerometers to detect tilting of slate devices. The resulting system supports fluid, minimally disruptive techniques for co-located collaboration by leveraging the proxemics of people as well as the proxemics of devices.